Efficacy of Ageratum conyzoides extracts against Giardia duodenalis trophozoites: an experimental study - Ai-rada Pintong; Jiraporn Ruangsittichai; Sumate Ampawong; Kanthinich Thima; Patchara Sriwichai; Narumon Komalamisra; Supaluk Popruk (BMC, 2020)
Abstract Background Giardia duodenalis causes giardiasis in humans, particularly in developing countries. Despite the availability of treatments, resistance to some of the commercial anti-Giardia drugs has been reported in addition to their harmful side effects. Therefore, novel treatments for giardiasis are required. In this study, we aimed to assess the in vitro activity of crude extracts of Ageratum conyzoides against G. duodenalis trophozoites. Methods Plants were classified into three groups based on their flower colors: white (W), purple (P), and white-purple (W-P). Plants were separately cut into leaf (L) and flower (F) parts. Changes in internal organelle morphology of trophozoites following exposure to crude extracts were assessed using transmission electron microscopy (TEM). In subsequent experiments, efficacy of the most active essential oils from crude extracts [half maximal inhibitory concentrations (IC50) ≤ 100 μg/mL] against G. duodenalis trophozoites was tested. In vitro anti-Giardia assays using essential oils were performed in the same way as those performed using crude extracts. Results LW-P and FP extracts showed high activity (IC50 ≤ 100 μg/mL) against G. duodenalis trophozoites, with IC50 ± SD values of 45.67 ± 0.51 and 96.00 ± 0.46 μg/mL, respectively. In subsequent experiments, IC50 ± SD values of LW-P and FP essential oils were 35.00 ± 0.50 and 89.33 ± 0.41 μg/mL, respectively. TEM revealed the degeneration of flagella and ventral discs of G. duodenalis trophozoites following exposure to crude extracts. Conclusion Crude LW-P and FP extracts of A. conyzoides showed the highest activity against G. duodenalis. Exposure to crude extract induced changes in the flagella and ventral discs of G. duodenalis trophozoites, which play important roles in attachment to the surface of mucosal cells. Our results suggest that the tested extracts warrant further research in terms of their efficacy and safety as giardiasis treatment.